2018
DOI: 10.1098/rsos.180757
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of organophosphorus pesticide residues in peanut and soya bean extracted solutions

Abstract: This study was performed to determine the storage stability of organophosphorus pesticide residues in high oil content commodity matrices, peanut and soya bean. The storage conditions included different types of solvents (ethyl acetate, acetone and hexane) and corresponding extracted matrix solutions, light and temperature. It was found that three pesticides degraded quickly especially in ethyl acetate solvent. They decreased greater than 30% when stored for 3 days at −20°C in ethyl acetate; the results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…There was no obvious selective degradation trend in syn- IZM and anti -IZM. According to the OECD standard, the compound was stable in analytical samples when the degradation rate was less than 30%. , In the present study, the maximum degradation rate of the four compounds in tomato at −20 °C within 36 weeks was 16.0%, indicating that the four compounds were stable in tomato at −20 °C within 36 weeks. These results were consistent with the storage stability results of a previous study of IZM on wheat, apple, orange, etc.…”
Section: Resultssupporting
confidence: 55%
“…There was no obvious selective degradation trend in syn- IZM and anti -IZM. According to the OECD standard, the compound was stable in analytical samples when the degradation rate was less than 30%. , In the present study, the maximum degradation rate of the four compounds in tomato at −20 °C within 36 weeks was 16.0%, indicating that the four compounds were stable in tomato at −20 °C within 36 weeks. These results were consistent with the storage stability results of a previous study of IZM on wheat, apple, orange, etc.…”
Section: Resultssupporting
confidence: 55%
“…The use of standard addition could eliminate the matrix effect and improve the test result accuracy, but it will waste time and chemicals in its preparation. Since pesticides could remain stable in sample extracts used as calibrants for several days, 20,21 and the stability study of isoprocarb and carbaryl in sample extracts of coffee beans was performed. The storage stability of the spike concentrations of 10, 50, and 100 mg kg −1 , which were stored at 25, 4, and −20 °C in clear and amber vials, respectively, was observed for 7 days.…”
Section: Preparation Of the Standard And Spiked Samplesmentioning
confidence: 99%
“…Widespread agricultural use of pesticides and home storage make them easily available for acts of self-harm in many rural households. Stability of organophosphorus pesticides is also important issue [43]. It was found that Malathion was more unstable than dichlorvos and diazinon; there was an over 70% loss in 90 days even at -20 °C in coarsely chopped form [44].…”
mentioning
confidence: 99%